Pleomorphic hyalinizing angiectatic tumor of the vulva: literature review based on a rare presentation - Silva, Eveline Cristina da; Abreu, Rodrigo Fonseca; Nascimento, Antônio Geraldo; Andrade, Louise De Brot (Autopsy and Case Reports, 2022)
Pleomorphic hyalinizing angiectatic tumor (PHAT) of soft tissues is a rare, non-metastatic tumor of unknown etiology and uncertain behavior, which may recur locally. There are few reports on this condition, and due to the rarity of the disease, its lineage has not yet been fully elucidated. The present study aims to report the case of an unusual entity observed for the first time in vulval topography. A female patient, 83 years old, presented with a tumor in the vulvar region that had evolved for approximately 4 months. Magnetic resonance imaging showed an expansive perineal formation of 8.5 × 3.5 cm, and a hemivulvectomy with a flap rotation was performed. The review of the slides revealed a mesenchymal lesion without significant atypia, which was richly vascularized. In the areas of interest, the immunohistochemical (IHC) study demonstrated positivity for CD34, estrogen, and progesterone receptors; it was negative for the other tested markers. Morphological findings associated with the IHC staining panel supported the diagnosis of PHAT. The main morphological features of PHAT are clusters of ectatic vessels of different sizes that show deposits of subendothelial and intraluminal fibrin. Fusiform and pleomorphic cells randomly arranged in leaves or long fascicles intermingle these vessels. It is essential to recognize this entity and consider it among the differential diagnoses of a mesenchymal lesion, given the wide variety of entities that comprise this group of lesions.